Analysis and future outlook of intra-Asia shipping - Xiao, Bowen (2018)
In recent years, the intra-Asia maritime trade has shown a significantly growth and huge potential. The Asian continent has become the world central for trading and shipping. With four countries, China, Japan, India, Russia top the five largest oil consuming countries in the world, the intra-Asia oil trading business are full of opportunities for different stakeholders. In oil trade business, the crude oil and petroleum product are the two major commodities. The increasing consumption for these two commodities by Asian countries makes a difference to the tanker market in Asian region because these two commodities are mainly transported by tanker vessel. With the prominent development of intra-Asia oil trade and tanker market shown in the past recent years, this project aims to analyze the current oil trade pattern and future outlook of intra-Asia tanker trade market. The project will focus on selected commodity demand and supply, government policies, infrastructure and facilities development. During the project, comprehensive literature reviews, search on secondary data, questionnaires with industrial professionals will be conducted to support the project. Finally, a conclusion will be proposed in respect of future opportunities, threats and uncertainties which aims to provide a guidance to different stakeholders in the industry.